5-(4-Hydroxy-3-methoxybenzyl)-1,3-thiazolidine-2,4-dione monohydrate - Xiong, Li-Yan (International Union of Crystallography, 2010)
In the title compound, C(11)H(11)NO(4)S·H(2)O, the five-membered thiazolidine ring is nearly planar, with a maximum deviation of 0.010 (2) Å. The dihedral angle between the thiazolidine and benzene rings is 49.16 (9)°. Intermolecular O—H⋯O and N—H⋯O hydrogen bonding is present in the crystal structure.